Lipid Extraction Methods from Microalgae: A Comprehensive Review - Ranjith Kumar, Ramanathan; Hanumantha Rao, Polur; Arumugam, Muthu (Frontiers in Energy Research, 2015)
Energy security has become a serious global issue and a lot of research is being carried out to look for economocially viable and environment-friendly alternatives. The only solution that appears to to meet the futuristic needs is the use of renewable energy. Although various forms of renewable energy are being currently used, the prospects of producing carbon-neutral biofuels from microalgae appears bright because of its unique features such as suitability of growing in open ponds required for production of a commodity product, high CO2-sequestering capability, ability to grow in wastewater/seawater/brackishwater and high lipid productivity. The major process constraint in the microalgal biofuel technology is the cost-effective and efficient extraction of lipids. The objective of this article is to provide a comprehensive review on various methods of lipid extraction from microalgae available till date, as well as to discuss their advantages and disadvantages. The article covers all areas of lipid extraction procedures including solvent extraction procedures, mechanical approaches and solvent-free procedures apart from some of the latest extraction technologies. A lot more research efforts are required in this area for successful implementation of this technology at a production scale.